Caracterização epidemiológica da toxoplasmose suína na região do alto sertão do estado de Sergipe - Silva, José Eduardo Marques da (2017)
Toxoplasmosis is a zoonosis of worldwide distribution caused by Toxoplasma gondii, an obligate intracellular protozoan parasite coccidia, which can infect humans and other warm-blooded animals, and the felids as definitive hosts in the life cycle. Among the diseases considered zoonotic, it has gained prominence, as about 30% of the world population is infected by T. gondii, causing significant economic losses to livestock. The swine species has received special attention from epidemiologists as an important source of infection to the human population due to the ingestion of raw and / or undercooked meat containing bradyzoite cysts. They were collected and examined 230 swine blood samples from creations from 45 properties of High Hinterland sergipano slaughtered in two slaughterhouses, one in the city of Nossa Senhora da Glória and the other in Canindé do São Francisco, both with municipal inspection service. After the collection, an epidemiological questionnaire was applied to the animals' original properties, with questions related to food and sanitary management, among others. The samples were processed for positivity in the laboratory Imunodot Diagnósticos in Jaboticabal-SP. The titration was conducted at the Laboratory of Infectious Diseases of Domestic Animals of the Federal Rural University of Pernambuco. The search for anti-T. gondii antibodies was performed through the Indirect Immunofluorescence Reaction (IFR) with a cut-off point of 1:64. Of animals sampled, 8.3% (19/230) were positive in the IFT with titles ranging from 64 to 1024. The objective was to verify the presence of anti- Toxoplasma gondii antibodies and identify the risk factors associated with infection Pigs raised in the high sertao of the state of Sergipe and slaughtered in the slaughterhouses of that region. Due to the importance of toxoplasmosis in public health, knowledge about its frequency in pigs raised in the Sergipe alto Sertão region may contribute to the establishment of disease control and prevention measures, resulting in better herd health in this region.